2023
DOI: 10.3389/fmed.2022.1075465
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone attenuates LPS-induced acute lung injury by regulating metabolic reprogramming of macrophage

Abstract: BackgroundAcute lung injury (ALI) is a life-threatening inflammatory disease without effective therapeutic regimen. Macrophage polarization plays a key role in the initiation and resolution of pulmonary inflammation. Therefore, modulating macrophage phenotype is a potentially effective way for acute lung injury. Cryptotanshinone (CTS) is a lipophilic bioactive compound extracted from the root of Salvia miltiorrhiza with a variety of pharmacological effects, especially the anti-inflammatory role. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…However, effective therapeutic agents for BPD treatment are scarce ( Poets and Lorenz, 2018 ). Previous studies have shown that CTS plays an important role in lung injury ( Jiang et al, 2019 ; Ye et al, 2022 ), and the anti-inflammatory and anti-fibrotic effects of CTS are gradually being explored ( Li et al, 2021 ). Accordingly, this study aimed to explore the anti-inflammatory and anti-fibrotic effects of CTS in a BPD model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, effective therapeutic agents for BPD treatment are scarce ( Poets and Lorenz, 2018 ). Previous studies have shown that CTS plays an important role in lung injury ( Jiang et al, 2019 ; Ye et al, 2022 ), and the anti-inflammatory and anti-fibrotic effects of CTS are gradually being explored ( Li et al, 2021 ). Accordingly, this study aimed to explore the anti-inflammatory and anti-fibrotic effects of CTS in a BPD model.…”
Section: Discussionmentioning
confidence: 99%
“…Six fields of view were randomly selected for each stained section for observation under a light microscope (magnification, ×40). Ye et al (2022) assessed the degree of inflammatory damage in the lung using a score based on four parameters: the degree of interstitial oedema, inflammatory cell infiltration, alveolar septal thickness and alveolar congestion level. The score was graded as follows: Level 0 was normal; Level 1 was 25%; Level 2 was 25%–50%; Level 3 was 50%–75%; and Level 4 was ≥75%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HE lung injury scores were calculated by light microscopic analysis of 4 parameters including alveolar septal thickness, interstitial edema, infiltration of inflammatory cells, and alveolar congestion/collapse. Each parameter was categorized into four grades: 0 = normal, 1 ≤ 25%, 2 = 25–50%, 3 = 50–75%, and 4 ≥ 75%, and the mean score of the four parameters was used to represent the overall lung injury [ 23 ].…”
Section: Methodsmentioning
confidence: 99%